Trusting AI in Finance: The Role of Psychological Traits and AI Literacy in Shaping User Behaviour Toward Robo-Advisors - Aini, Sukma (The South East Asian Journal of Management, 2025)
Research Aims: This study investigates the influence of psychological traits, risk tolerance, trust propensity, and AI literacy on trust in robo-advisors and subsequent financial behaviour within Indonesia’s expanding fintech landscape. Design/Methodology/Approach: Data were collected through a survey of 235 Indonesian users with prior robo-advisor experience, and the hypotheses were tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). Research Findings: The results revealed that risk tolerance, trust propensity, and AI literacy significantly predicted financial behaviour, both directly and indirectly, through their positive effects on trust in AI. Trust emerged as a central mediating mechanism, particularly for trust propensity and AI literacy, highlighting its role as a psychological gateway linking user dispositions to behavioural outcomes. Theoretical Contribution/Originality: By extending the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) with behavioural finance and cognitive trust theory, this study provided a more comprehensive explanation of AI adoption in financial services. Managerial Implication in the South East Asian Context: The results offer practical implications for fintech providers in Indonesia and Southeast Asia, underscoring the importance of explainable AI, transparent data-use disclosures, and culturally attuned system design that accommodates diverse risk profiles and digital literacy levels. Research Limitation & Implications: Limitations include the cross-sectional design, reliance on self-reported data, and an urban-centric sample. Future research should incorporate rural populations, adopt longitudinal approaches, and explore cultural dimensions of trust.